Protective actions of vitamin D, anandamide and melatonin during vascular inflammation: Epigenetic mechanisms involved - Martín Giménez, Virna Margarita; Chuffa, Luiz Gustavo A. [UNESP]; Simão, Vinícius Augusto [UNESP]; Reiter, Russel J.; Manucha, Walter (Elsevier, 2022)
Vascular inflammation is one of the main activating stimuli of cardiovascular disease and its uncontrolled development may worsen the progression and prognosis of these pathologies. Therefore, the search for new therapeutic options to treat this condition is undoubtedly needed. In this regard, it may be better to repurpose endogenous anti-inflammatory compounds already known, in addition to synthesizing new compounds for therapeutic purposes. It is well known that vitamin D, anandamide, and melatonin are promising endogenous substances with powerful and wide-spread anti-inflammatory properties. Currently, the epigenetic mechanisms underlying these effects are often unknown. This review summarizes the potential epigenetic mechanisms by which vitamin D, anandamide, and melatonin attenuate vascular inflammation. This information could contribute to the improvement in the therapeutic management of multiple pathologies associated with blood vessel inflammation, through the pharmacological manipulation of new target sites that until now have not been addressed.
Keywords: Anandamide; Anti-inflammatory agents; Epigenetics; Melatonin; Vascular inflammation; Vitamin D